The diagenetic and tectonic significance of hydrocarbon accumulation in the southern Junggar Basin, NW China. (22nd December 2017) - Hu, Hanwen; Tian, Xiaoru; Zhang, Jian; Zhuo, Qingong; Jia, Chengzao; Guo, Zhaojie
Abstract : The Jurassic petroleum system plays an increasingly important role in petroleum explorations in the southern Junggar Basin. To assess the hydrocarbon distribution and the accumulation history of the Jurassic reservoirs in this area, we carried out reservoir petrographic, fluorescence spectroscopic, and fluid inclusion petrographic analyses on the core and cutting samples from the QQ‐2 well in the Qigu Anticline. The oil accumulation has the partiality for high‐quality sandstone reservoirs that have the high porosity and permeability with values of 14–18% and (1–450) × 10 −2  μm 2, respectively, in the Middle Jurassic Toutunhe Formation (J2 t) reservoirs. The pores are big with average diameters of 60–100 μm, and the pore throats are wide with values of 3.45–6.92 μm in the oil reservoirs. The intergranular pores survive thanks to the poor compaction and the poor cementation, and the dissolved and mould pores develop attributed to the strong dissolution in the oil reservoirs. Two episodes of oil charging and one episode of gas invasion were identified in the Middle Jurassic reservoirs in the southern Junggar Basin. The low‐maturity paleo‐oil charged the sandstone reservoirs at about 35 Ma when the paleo‐traps took shape during the Cretaceous–Eocene. A large number of faults and anticlinal traps was developed in the southern Junggar Basin at about 7 Ma, caused by the reactivation of the Tianshan Mountains in the late Cenozoic. Simultaneously, the leakage of the paleo‐oil, the accumulation of late oil, and the gas invasion all took place. Fault activities led to the leakage of paleo‐oil and helped the oil and gas accumulate in the Middle Jurassic reservoirs in the anticlinal trap shaping at about 7–8 Ma in the southern Junggar Basin.